2019
DOI: 10.14763/2019.3.1420
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on ethics and the laws of artificial intelligence

Abstract: The continuous interaction between intelligent devices, sensors and people points to the increasing number of data being produced, stored and processed, changing, in various aspects and increasingly, our daily life. This increasing connectivity and symbiotic interaction among humans and intelligent machines brings significant challenges for the rule of law and contemporary ethics. Do machines have morality? What legal liability regime should we adopt for damages arising from increasingly advanced artificial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…They represent people on stock exchanges, and make decisions on behalf of their owners; they manage several economic processes without direct human contribution and they serve marketing purposes (Dahiyat, 2021) . This very brief enumeration clearly demonstrates that electronic humanoids have diverse economic functions, and their significance is expected to increase continually (Magrani, 2019) . The increasingly vital role of AI in the economy should not, however, lead us to the conclusion that robots must be vested with the same economic rights as ordinary people .…”
Section: Robots As Economic Actorsmentioning
confidence: 99%
“…They represent people on stock exchanges, and make decisions on behalf of their owners; they manage several economic processes without direct human contribution and they serve marketing purposes (Dahiyat, 2021) . This very brief enumeration clearly demonstrates that electronic humanoids have diverse economic functions, and their significance is expected to increase continually (Magrani, 2019) . The increasingly vital role of AI in the economy should not, however, lead us to the conclusion that robots must be vested with the same economic rights as ordinary people .…”
Section: Robots As Economic Actorsmentioning
confidence: 99%
“…AI systems are increasingly taking on tasks and decisions that are traditionally performed by humans. An essential and ethical question that arise from this is that whether AI system should be endowed with "personhood" and moral or legal agency rights [58].…”
Section: B) Impact On Human Psychologymentioning
confidence: 99%
“…On the other hand, the application of the traditional paradigm of civil liability, especially when conceived as a strict liability regime, would expose producers and programmers to unpredictable and potentially unlimited claims for civil liability, with no possibility of reducing the risks by increasing investments in safety (with regard to damage following “unforeseeable” behaviour of AI algorithms). Therefore, it is likely that such an application 19 would prevent them from entering the market or developing it, thereby hampering technological progress (what is sometimes called the risk of “technology chilling”: Montagnani and Cavallo 2020 ; Viscusi and Moore 1991 ; Huber and Litan 1991 ; Parchomovsky and Stein 2008 ; Morgan 2017 ; Magrani 2019 ; Policy Department for Citizens’ Rights and Constitutional Affairs 2020 ; EU Independent High-Level Expert Group On Artificial Intelligence 2019a , b ; Bertolini 2015 ; Pellegatta 2019 ; Palmerini and Bertolini 2016 ).…”
Section: Ai and Civil Liability: The Problem(s)mentioning
confidence: 99%
“…Law scholars have observed that current civil liability legislation can be an obstacle to the development of artificial intelligence and the exploitation of the following benefits (Montagnani and Cavallo 2020 ; Viscusi and Moore 1991 ; Huber and Litan 1991 ; Parchomovsky and Stein 2008 ; Morgan 2017 ; Magrani 2019 ; Policy Department for Citizens’ Rights and Constitutional Affairs 2020 ; EU Independent High-Level Expert Group On Artificial Intelligence 2019a , b ; Bertolini 2015 ; Pellegatta 2019 ; Palmerini and Bertolini 2016 ). A similar obstacle has been observed, in the past, with regard to medical civil liability.…”
Section: A Proposal: the Need To Relieve Producers And Programmers Frmentioning
confidence: 99%